Clarification of shear deformation behavior in Fe–Si amorphous alloys by molecular dynamics - Chieko Kuji; Narumasa Miyazaki; Masayoshi Mizutani; Keita Shimada; Nobuki Ozawa; Momoji Kubo; Tsunemoto Kuriyagawa (Materials & Design)
Two Fe85Si15 amorphous alloy models were created based on molecular dynamics with different cooling rates of 1010 K/s (slower model) and 1012 K/s (faster model) and examined the effects of atomic structure on the mechanical properties and shear band (SB) propagation behavior, which determines the shear processing quality. Voronoi analysis of the short-range ordered structures (SRO) revealed that the slower model has more full icosahedral SROs than the faster model, and Young’s modulus and tensile strength were 11 % and 14 % higher than those of the faster model, respectively. Indentation calculations presuming crack propagation during shear processing were then performed on both models. Only in the case of the slower model, the icosahedral SRO in the SB changed to intermediate structures, increasing the distorted body-centered cubic (BCC) structure. The SB in the faster model spread out isotropically from the indenter, whereas that in the slower model propagated in the indent direction. These results indicate that intermediate and distorted BCC structures in the SB provide directionality to the SB propagation and suggest that the slower model, in which cracks propagate toward the shear direction of the material and break it in a straight line, may produce a higher-quality surface in shear processing.